Mechanical properties and environmental stress cracking resistance of rubber toughened polyester/kenaf composite (eXPRESS Polymer Letters)
In this study rubber-toughened polyester-kenaf fibre composites were prepared by adding various percentages of kenaf fibre in unsaturated polyester resin and subsequently cross linked using a mixture of organic peroxide methyl ethyl ketone and cobalt octanoate. Three percent (3%) of liquid natural rubber (LNR) were added as a toughening agent. The mechanical properties of the composites were evaluated by impact and flexural testing. Environmental stress cracking resistance (ESCR) of polyester-kenaf composite in acid and base medium was also studied. It was found that the addition of LNR increased impact strength by about 66% and flexural strength by 70%. Measurement of ESCR shows that the composite has the fastest diffusion rate in acid medium, followed by that in base medium and then without medium. Bonding mechanisms were assessed by scanning electron microscope and FTIR analysis.